The Implementation of Ulul Ilmi Values in Dormitory Parenting to Support Students’ Mental Health: Penerapan Nilai Ulul Ilmi dalam Pengasuhan Asrama untuk Mendukung Kesehatan Mental Mahasiswa - Indah Sari; Nurti Budiyanti; Kokom st Komariah (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
This community service program aims to develop and implement a boarding school parenting model based on ulul ilmi values to support university students’ mental health and contribute to quality education. The program was carried out using a Participatory Action Research (PAR) approach involving 150 students living in a university dormitory. The stages of implementation included needs assessment, participatory workshops, guided religious activities such as congregational prayer, dhikr, and Qur’an recitation, as well as reflective evaluation. The results of the program indicate positive changes in students’ mental well-being, reflected in improved emotional stability, discipline, self-confidence, and academic engagement. The integration of spiritual values functioned as an effective coping mechanism in helping students manage academic and social pressures. Overall, the ulul ilmi character-based parenting model, which synergizes spiritual, intellectual, and socio-moral dimensions, contributes to the creation of a supportive academic ecosystem for mentally resilient students. This program has practical implications for the development of a prototype of ulul ilmi character-based boarding school parenting modules.